Addressing challenges in pediatric thrombosis: a comprehensive guideline development - Wang, Yin; Yin, Qinan; Liao, Jiangting; Wang, Na; Li, Li; Li, Siyan; Zhang, Qingxia; Yu, Feifei; Luo, Jianchun; Wang, Hongmei; Hu, Die; Li, Wenyi; et al. (Frontiers in Pediatrics, 2025)
BackgroundPediatric thrombosis is a relatively rare but severe condition in the field of pediatrics, with far-reaching consequences. Recent studies have indicated a rising incidence of this disease in children over the years. Additionally, the pharmacological treatment of thrombotic diseases in children faces numerous challenges. Due to significant physiological differences between children and adults, guidelines for the prevention and treatment of thrombotic diseases in adults cannot be directly applied to pediatric patients.PurposeA systematic review of the existing evidence-based medical literature should be conducted to propose pharmacological prevention and treatment recommendations for pediatric thrombotic diseases. Developing a comprehensive and practical pharmacotherapy guideline for the prevention and treatment of pediatric thrombotic diseases is essential to enhancing the rational use of medications in managing these conditions in children.MethodsThe guideline development followed the World Health Organization's (WHO) Handbook for Guideline Development. This involves systematically searching and extensively collecting data on common medication issues in the prevention and treatment of pediatric thrombosis nationwide. The Delphi method was used to survey experts and identify the clinical issues to be included. Subsequently, a systematic literature review was conducted to evaluate existing primary studies, systematic reviews, and guidelines or consensus statements from professional organizations. The quality of the evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. The Delphi method was employed again to reach a consensus on the recommendations and evidence levels. This process was culminated in the development of the Guideline for Pharmacological Management of Thrombotic Diseases in Children.ResultsDuring the guideline development process, a total of 29 clinical issues were collected and evaluated by 78 experts in clinical pharmacy and clinical medicine. Through two rounds of surveys, 13 clinical issues were selected. Under the supervision of two methodologists, 13 clinical pharmacotherapy recommendations were formulated.ConclusionBy conducting a comprehensive assessment of the feasibility and safety of clinical practices, the guideline provides specific anticoagulant medication recommendations for pediatric healthcare professionals. This will help enhance the prevention and treatment of pediatric thrombosis, promoting more standardized and effective medical practices.